2014
DOI: 10.1111/kykl.12056
|View full text |Cite
|
Sign up to set email alerts
|

Trading Effects of the FIFA World Cup

Abstract: Summary This study analyzes the trading effects of FIFA World Cup in two dimensions. First, we show that participating in the World Cup significantly increases exports from the participant countries to the host countries, relative to a control group of non‐participants. Second, we demonstrate that trade is reasonably higher for host‐participant pairs compared to other country pairs. We also provide dynamic estimates for both cases and offer plausible arguments and important channels for our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In furtherance of this goal we utilize international sporting events which have in the past been used to great effect, from market analysis (Avsar and Unal, ), and superstar effects (Torgler and Schmidt, ) to the effect of stress and environment on decision making (Caruso et al, ; Torgler, ). Not only are sporting events very close to an experimental environment with cleanly generated data and most external confounds controlled by rules and referees (Goff and Tollison, ), but it is a winner take all competition with very real stakes.…”
Section: Introductionmentioning
confidence: 99%
“…In furtherance of this goal we utilize international sporting events which have in the past been used to great effect, from market analysis (Avsar and Unal, ), and superstar effects (Torgler and Schmidt, ) to the effect of stress and environment on decision making (Caruso et al, ; Torgler, ). Not only are sporting events very close to an experimental environment with cleanly generated data and most external confounds controlled by rules and referees (Goff and Tollison, ), but it is a winner take all competition with very real stakes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Avsar and Unal (2014), using bilateral trade data for a panel of countries, found a positive trading effect of the World Cup.…”
Section: Can Sports Promote Exports?mentioning
confidence: 97%
“…15 The size of the estimated impact is furthermore in line with previous studies. For instance, Rose and Spiegel (2011) found that trade is around 30 percent higher for countries that have hosted the Olympics, and Avsar and Unal (2014) estimated that trade is about 18-20 percent higher for host-participant combinations when compared to other country pairs in the years of the World Cup. Table 4 provides results of addition robustness checks and what this table shows is that the main findings are robust to several tests.…”
mentioning
confidence: 99%
“…Finally, this investigation is related to the literature that uses sports data to analyze an economic phenomena, as Kolev et al () who analyze whether agents act rationally using data on NHL games, or Schön et al () who analyze which managers put more effort into the firm, using golf handicaps data. Avsar and Unal () analyze whether an sport event, the FIFA World Cup, has a positive effect on trade; other papers, such as Torgler () and Bakkenbüll and Kiefer () analyze the factors that determine success in sports, such as football and tennis respectively. We contribute to this literature analyzing what determines success at chess, and how differences in the number of expert chess players are related to variations in fundamental and granular comparative advantage across countries.…”
Section: Related Literaturementioning
confidence: 99%